Hubungan Kemandirian dan Motivasi Belajar Terhadap Hasil Belajar Kognitif Biologi Peserta Didik pada Pembelajaran Online di SMA Muhammadiyah Se-Kota Palembang: (The Relationship between Independence and Learning Motivation on Biological Cognitive Learning Outcomes of Students in Online Learning at Muhammadiyah High Schools throughout Palembang City) - Tri Fathan; Saleh Hidayat; Sri Wardhani (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2022)
This study aims to determine the relationship between independence and learning motivation on cognitive learning outcomes of Biology Students in online learning at Muhammadiyah high schools throughout Palembang. The research design used is descriptive quantitative research. Data collection techniques using a questionnaire sheet and learning outcomes of cognitive Biology students. The data obtained were analyzed using the significance test. The research subjects were students of class X and XI in the even semesters of the 2019/2020 school year, the sampling technique used the slovin formula. The results obtained after using the significance test at Muhammadiyah high schools in Palembang City, it is known that the significance value is < 0.05, which means (1) there is a relationship between learning independence and cognitive biology learning outcomes of students in online learning at Muhammadiyah high schools throughout Palembang, (2) there is a relationship between learning independence and cognitive biology learning outcomes of students in online learning at Muhammadiyah high schools throughout the city of Palembang and (3) there is a relationship between independence and learning motivation on students' cognitive biology learning outcomes in online learning at Muhammadiyah high schools throughout the city Palembang. Key word : : Independence, Motivation and Learning Outcomes. Â ABSTRAK Penelitian ini bertujuan untuk mengetahui hubungan antara kemandirian dan motivasi belajar terhadap hasil belajar kognitif BiologiPeserta Didik pada pembelajaran online di SMA Muhammadiyah se-Kota Palembang.Rancangan penelitian yang digunakan berupa penelitian deskriptif kuantitatif. Teknik pengumpulan data dengan menggunakan lembar angket dan hasil belajar kognitif Biologi peserta didik. Data yang diperoleh dianalisis menggunakan uji signifikansi. Subjek penelitian adalah peserta didik kelas X dan XI pada semester genap di tahun pelajaran 2019/2020, teknik pengambilan sampel menggunakan rumus slovin. Hasil penelitian diperoleh setelah menggunakan uji signifikansi di SMA Muhammadiyah se-Kota Palembang diketahui bahwa nilai signifikansi< 0,05, yang artinya (1) terdapat hubungan kemandirian belajar terhadap hasil belajar kognitif Biologi peserta didik pada pembelajaran online di SMA Muhammadiyah se-Kota Palembang, (2) terdapat hubungan kemandirian belajar terhadap hasil belajar kognitif Biologi peserta didik pada pembelajaran online di SMA Muhammadiyah se-Kota Palembang dan (3) terdapat hubungan kemandirian dan motivasi belajar terhadap hasil belajar kognitif Biologi peserta didik pada pembelajaran online di SMA Muhammadiyah se-Kota Palembang. Kata Kunci: Kemandirian, Motivasi dan Hasil Belajar.